Effects of planting configuration and row spacing on growth and production of potato under mulched condition in Dadeldhura, Nepal - Dhakal, Roshan; Joshi, Binod; Bharati, Santosh; Dhakal, Shiva Chandra; Joshi, Khem Raj (Journal of Agriculture and Natural Resources, 2019)
An experiment was conducted at the research site of Dadeldhura, Nepal in 2019 to identify optimum plant spacing for potato under mulched condition. Three levels of inter row spacing; 60 cm with single row per bed (1RB), 45 cm with double row per bed (2RB) and 30 cm with triple row per bed (3RB) and intra row spacing (20, 30 and 40 cm) were laid out in factorial randomized complete block design with three replications. Results showed that there was significant difference (p